Improving Students’ Reading Comprehension By Implementing Top-Down Processing Strategy - Abdul baqi, Fuad; Apriani, Reni (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
This study entitled “Improving Students’ Reading Comprehension by Implementing Top-Down Processing Strategy”. Reading is an important skill that has to be taught in senior high school. From reading a text, the reader can get many knowledge and information. While, Top-Down Processing Strategy is one of strategies that can encourage students’ background knowledge to assist them in comprehending their reading. This study aimed at recognizing whether Top-Down Processing strategy increases students’ reading comprehension, and also to finding out students’ obstacles in learning reading comprehension by using Top-Down Processing strategy. To gain the data, the researchers conducted field research at SMAN 3 by implementing three techniques, namely: Experimental teaching, test and questionnaire. In choosing the sample the researcher used purposive sampling.